O impacto da invasão por Hedychium coronarium J. König (Zingiberaceae) em áreas ripárias - Zanatta, Mariane Patrezi (2019)
Riparian environments are increasingly being modified by human activities and this causes changes in vegetation dynamics. Native species are being replaced by exotic and invasive ones. Impacts of plant invasions in these environments include changes in ecosystem processes, organic matter entry, nutrient cycling, microbial communities, decomposition, and soil attributes. We evaluated the impact of Hedychium coronarium on litter biomass production, nutrient cycling and decomposition in invaded and noninvaded areas. In addition, we have looked at general trends in research on plant invasions in riparian environments in last decades. The one-year study in two distinct riparian environments showed that litter production does not differ between invaded and non-invaded areas. Moreover, this production is not uniform throughout the year, and there is an increase in the dry season. The impact of H. coronarium invasion on litter and soil nutrients depends on the ecological context of the environment and soil attributes, mainly the texture; in nitrogen-poor soils with a sandy clay loam texture, H. coronarium appears to increase the total N concentration in the soil. In the decomposition, our results showed a significant effect of the environmental treatment (non-invaded area) and the interaction between the seasonal treatment and the type of detritus (higher decomposition in dry season with vegetal species and dry season with mixed detritus too). We also found a higher amount of organic matter (OM) in the non-invaded area. In addition, studies with invasion in riparian environments are recent, this topic had an increase in a number of publications only in 2007. We conclude that to better understand the invasion of H. coronarium in riparian environments it is necessary to consider the species in each context and environment of invasion; besides the importance of studying the soil in these types of studies.